The Water, Energy, and Food Nexus: Health is yet Another Resource - Nuwayhid, Iman; Mohtar, Rabi (Frontiers in Environmental Science, 2022)
Abstract This paper highlights the place for Health (H) in the Water, Energy, and Water (WEF) nexus. It reviews the background in the WEF literature, describes how it can be approached, and makes the case that now is the time to integrate health into the WEF Nexus. The basis for our argument is that although the nexus concept of food, energy, and water is relatively recent, it has been adopted by several UN agencies and international organizations and will continue to draw emphasis in research, politics, and communications of the scientific community.